LIVRO DISCUTE A NATUREZA DA TRADIÇÃO EM ALASDAIR MACINTYRE E GEORGE LINDBERG - Aires de Carvalho, Helder Buenos (Pensando - Revista de Filosofia, 2015)
Livro de David TRENERY, "Alasdair MacIntyre, George Lindbeck, and the Nature of Tradition. Eugene, Pickwick Publications, 2014". What should we believe, and why should we believe it? This book addresses these questions through a critical exposition of the work of the contemporary philosopher Alasdair MacIntyre and of the theologian George Lindbeck, the father of postliberal theology. The book argues that MacIntyre's philosophical development can be seen as a response to the question of how belief in a comprehensive metaphysical system can be justified. Such a system provides its believers with an account of the nature of the universe and human nature, and a basis for their ethical reasoning and action. The book draws on Lindbeck's cultural-linguistic account of religion to argue that such a system is primarily a way of interpreting the world and the place of humanity within it, rather than a speculative theory. The justification of belief in such systems can be understood in terms of MacIntyre's account of tradition-constituted rationality, provided that this notion of rationality is made more specific by the incorporation of elements of Lindbeck's theology. Equally, the book argues that Lindbeck's theology can be strengthened by the incorporation of elements drawn from MacIntyre's work. This book will be of value to students of philosophy and theology and to the general reader who is interested in the question of the grounds of belief. David Trenery (born 1950) studied philosophy of religion in the late 1960s and early 1970s before marriage and the need to earn an honest living made him become first a social worker, and later a senior manager in social work organisations. A career shift into the UK's Open University in 2005 enabled him to return to the academic world and gave him the opportunity to renew his earlier interest in the foundations of religious belief. He was awarded a PhD by Nottingham University in the UK in 2013. His book "Alasdair MacIntyre, George Lindbeck and the Nature of Tradition" is based on his dissertation, and explores the question of what it is legitimate to believe and why. He is now combining his interest in social work and Alasdair MacIntyre's philosophy by exploring the relationship between social work values and virtue ethics.